PENGARUH MOTIVASI, DISIPLIN, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT.HOTMA ARTA JAYA MANDIRI - Simangunsong, Elisabeth; Pasaribu, Agnes; Sitanggang, Darna; Sagala, Roslinda; Bangun, Kristina (LPPM Universitas Katolik Santo Thomas Medan, 2023)
This study aims to determine and explain the influence of motivation, discipline and compensation on employee performance at PT.Hotma Arta Jaya Mandiri. Data collection was carried out quantitatively, with 56 respondents who were taken using saturated or census sampling. Data analysis in this study used SPSS version 23. From the results of partial testing the t test showed that motivation, discipline and compensation had a positive and significant effect on employee performance. From the F test shows that simultaneously motivation, discipline and compensation have a significant effect on employee performance. cloud. The coefficient of determination (R Sqare) is 0.627, meaning that employee performance can be explained by the motivation, discipline and compensation variables of 62.7% while the other 37.3% is not explained in this study.